São Francisco River: a place-territory - Silva, Cícero Bezerra da (Revista Cerrados, 2020)
The article aims to first discuss the theoretical and conceptual foundations that guide the geographical categories place and territory and, based on their respective similarities, present a hybrid / composed reading of these categories, forming the place-territory. These similarities are based on the processes of material and symbolic appropriation, on the identities and the sense of belonging that make up these categories. As an empirical reference for analysis, the São Francisco river is used in its low course, whose spatiality is characterized by the diverse complexity of uses and appropriations that are revealed both by reading the place and by reading the territory. Thus, this complexity observed in the experiences with the river and in semi-structured interviews outlined the fundamentals that make riverside spatiality a place-territory.